Proline 36 of the Factor XIII Activation Peptide Plays a Crucial Role in Substrate Recognition and Zymogen Activation - Li, Bojun; Billur, Ramya; Maurer, Muriel C.; Kohler, Hans P.; Raddatz Müller, Pascale; Alberio, Lorenzo; Schroeder, Verena (Thrombosis and Haemostasis, 2018)
The activation peptide of blood coagulation factor XIII (AP-FXIII) has important functions in stabilizing the FXIII-A2 dimer and regulating FXIII activation. Contributions of many of its 37 amino acids to these functions have been described. However, the role of proline 36, which is adjacent to the thrombin cleavage site at Arg37, has not yet been studied in detail. We approached this question when we came across a patient with congenital FXIII deficiency in whom we detected a novel Pro36Ser mutation. We expressed the mutant FXIII-A Pro36Ser protein in Chinese hamster ovary cells and found that this mutation does not influence FXIII-A expression but significantly inhibits proteolytic activation by thrombin. The enzymatic transglutaminase activity is not affected as it can be induced in the presence of high Ca2+ concentrations. We performed nuclear magnetic resonance analysis to investigate AP-FXIII–thrombin interactions, which showed that the mutant Ser36 peptide binds less well to the thrombin surface than the native Pro36 peptide. The Arg37 at the P1 position still makes strong interactions with the active site cleft but the P4–P2 residues (34VVS36) appear to be less well positioned to contact the neighbouring thrombin active site region. In conclusion, we have characterized a novel mutation in AP-FXIII representing only the fourth case of the rare FXIII-A type II deficiency. This case served as a perfect in vivo model to shed light on the crucial role of Pro36 in the proteolytic activation of FXIII-A. Our results contribute to the understanding of structure–function relationship in FXIII.
Keywords: coagulation factor XIII; factor XIII activation peptide; congenital factor XIII deficiency